AN ANALYSIS OF THE TRANSLATION OF THE PHRASAL VERBS IN THE NOVEL "THE UNDOMESTIC GODDESS" WRITTEN BY SOPHIE KINSELLA - Hadi, Belani Asmara (2014)
Penelitian yang berjudul "Analisis Penerjemahan Kata Kerja Berfrase di dalam Novel 'The Undomestic Goddess' Karya Sophie Kinsella" ini mengkaji tata cara penerjemahan kata-kata kerja berfrase dari bahasa sumber (Inggris) ke bahasa target (Indonesia), mengkaji kesesuaian penerjemahan dari novel versi terjemah dan mengkaji manfaat penggunaan kata-kata kerja berfrase dalam komunikasi di dalam kelas Bahasa Inggris untuk pengajaran EFL di tingkat SMA kelas X. Penelitian ini menggunakan metode kualitatif deskriptif untuk menyajikan data yang terdapat pada novel. Digunakan 120 kata kerja berfrase sebagai sampel dari novel. Proses pengumpulan data dilakukan dengan menggunakan metode sampel acak (random sampling method). Proses analisis data dikategorikan dengan merujuk pada Konstruksi Kata Kerja Berfrase yang digagas oleh Brown (2002) dan beberapa strategi penerjemahan yang merujuk pada Baker (1992, hal.85-92), Newmark (1988), Larson (1984), dan Vinay dan Darbelnet (1958) dalam Venuti (2000, hal.84-93). Dari penelitian ditemukan bahwa strategi penerjemahan "paraphrase" dari Baker (1992, hal.85-92) memiliki frekuensi tertinggi yakni 81.67% yang diterapkan pada 98 sampel dari 120 kata kerja berfrase sedangkan frekuensi tertinggi dari strategi penerjemahan yang merujuk pada Newmark, Larson dan Vinay dan Darbelnet yakni strategi penerjemahan "faithful" (Newmark, 1988), atau "inconsistent mixture" (Larson, 1984), atau "calque" (Vinay and Darbelnet (1958) dalam Venuti (2000, hal.84-93)) yang diterapkan pada 60 sampel dari 120 sampel kata kerja berfrase. Berdasarkan hasil penelitian, novel versi terjemahan sudah memenuhi kriteria dari sebuah terjemahan yang baik yang dikemukakan oleh Massoud (1988) dalam Barus (2010), serta memenuhi faktor-faktor pertimbangan dalam penerjemahan yang diungkapkan oleh Barnwell dalam Abdullah (1996) yang dikutip dari Barus (2010) dan juga memenuhi syarat dari karakteristik penerjemahan yang ideal berdasarkan Denoun (2004) dalam Barus (2010). Penelitian ini juga memberikan kontribusi yang positif terhadap pengajaran EFL, terutama penggunaan kata kerja berfrase transitive, inseparable dalam kegiatan komunikasi belajar yang informal antara guru dengan para siswa di kelas X dan penggunaannya da pat meningkatkan pembendaharaan kosakata kata kerja berfrase pada para siswa. The research paper entitled "An Analysis of the Translation of the Phrasal Verbs in the Novel 'The Undomestic Goddess' written by Sophie Kinsella" aims to find out the ways the phrasal verbs are translated from the source language (English) into the target language (Indonesian), the appropriateness of the translation version of the novel and the benefits of the phrasal verbs usage in English classroom communication for EFL teaching at the high school level grade X. This research used descriptive qualitative method to present the data gained from the novel. Those are 120 phrasal verbs as the samples of the data from the novel. The data collection was conducted by using a random sampling method. The data was categorized according to Brown's construction of phrasal verbs (2002) and several translation strategies in regard to Baker (1992, p.85-92), Newmark (1988), Larson (1984), and Vinay and Darbelnet (1958) in Venuti (2000, p.84-93). From the research, it was found that paraphrase translation strategy from Baker (1992, p.85-92) has the highest frequent of all 81.67% which were applied in 98 items of 120 phrasal verbs while the highest frequency of the translation strategies of Newmark, Larson and Vinay and Darbelnet is faithful translation strategy (Newmark, 1988), or inconsistent mixture (Larson, 1984), or calque (Vinay and Darbelnet (1958) as cited in Venuti (2000, p.84-93)) which were applied in 60 items of 120 phrasal verbs samples. From the findings of the research, the translation version of the novel fulfills the criteria of a good translation proposed by Massoud (1988) as cited in Barus (2010); covers the factors of translation judgment proposed by Barnwell in Abdullah (1996) as cited in Barus (2010); and also entails the characteristic of ideal translation according to Denoun (2004) as cited in Barus (2010). This research also gave a positive contributions to EFL teaching, especially in the use of transitive, inseparable phrasal verbs in teacher-students informal learning communication in grade X and it could improve students' vocabulary of phrasal verbs. The research paper entitled "An Analysis of the Translation of the Phrasal Verbs in the Novel 'The Undomestic Goddess' written by Sophie Kinsella" aims to find out the ways the phrasal verbs are translated from the source language (English) into the target language (Indonesian), the appropriateness of the translation version of the novel and the benefits of the phrasal verbs usage in English classroom communication for EFL teaching at the high school level grade X. This research used descriptive qualitative method to present the data gained from the novel. Those are 120 phrasal verbs as the samples of the data from the novel. The data collection was conducted by using a random sampling method. The data was categorized according to Brown's construction of phrasal verbs (2002) and several translation strategies in regard to Baker (1992, p.85-92), Newmark (1988), Larson (1984), and Vinay and Darbelnet (1958) in Venuti (2000, p.84-93). From the research, it was found that paraphrase translation strategy from Baker (1992, p.85-92) has the highest frequent of all 81.67% which were applied in 98 items of 120 phrasal verbs while the highest frequency of the translation strategies of Newmark, Larson and Vinay and Darbelnet is faithful translation strategy (Newmark, 1988), or inconsistent mixture (Larson, 1984), or calque (Vinay and Darbelnet (1958) as cited in Venuti (2000, p.84-93)) which were applied in 60 items of 120 phrasal verbs samples. From the findings of the research, the translation version of the novel fulfills the criteria of a good translation proposed by Massoud (1988) as cited in Barus (2010); covers the factors of translation judgment proposed by Barnwell in Abdullah (1996) as cited in Barus (2010); and also entails the characteristic of ideal translation according to Denoun (2004) as cited in Barus (2010). This research also gave a positive contributions to EFL teaching, especially in the use of transitive, inseparable phrasal verbs in teacher-students informal learning communication in grade X and it could improve students' vocabulary of phrasal verbs.